Câncer de próstata : incidência, mortalidade e sobrevida de residentes em Cuiabá e Várzea Grande - Evangelista, Flávio de Macêdo (2022)
Prostate cancer was the second most frequent and the fifth leading cause of cancer death among men in 2020 worldwide. It is important to know the epidemiological picture of cancer so that we can advance in prevention and control. Objective: To analyze the incidence, mortality and survival from prostate cancer in men living in Cuiabá and Várzea Grande, from 2000 to 2016. Methods: Study carried out in the cities of Cuiabá and Várzea Grande that analyzed the incidence, mortality and survival of prostate cancer. Data were obtained through the Population-Based Cancer Registry (RCBP) and Mortality Information System (SIM), from an extension project developed at the Instituto de Saúde Coletiva of the Federal University of Mato Grosso and entitled “Cancer and Its Diseases”. Associated Factors: Analysis of Population-Based and Hospital Registry of Mato Grosso”. Incidence and mortality rates for prostate cancer were calculated by year (2000 to 2016) and by age group, dividing the number of new cases by the population and multiplying by 100,000 inhabitants. Joinpoint method, calculating the annual percentage change (APC) and Average Annual Percentage Change (AAPC) using the Jointpoint Regression Program software. To calculate survival, a probabilistic relationship was performed between the cases registered in the RCBP between 2008 and 2012 and in the SIM between 2008 and 2017, using the RecLink III software. The Kaplan-Meier estimator method was used to analyze the survival curves and the semiparametric Cox proportional hazards model to estimate the hazard functions (H(t)), with the hazard ratio (HR) and their respective intervals of confidence (95%CI), according to age group. The analysis was performed using Stata software version 16.0. Results: From 2000 to 2016, 3,671 new cases and 892 deaths from prostate cancer were recorded in Cuiabá and Várzea Grande. The average of rates in the period (100,000 inhabitants) was 87.96 for incidence and 20.22 for mortality. There was a downward trend in the incidence rate for all ages from 2006 to 2016 (APC=-3.2%) and for men aged 80 years and over from 2000 to 2016 (APC=-3.0%), as well as increasing trend in the mortality rate in men aged 60–69 years from 2000 to 2009 (APC=3.2%). The probability of specific survival at five years was 79.6% (95%CI: 77.2; 81.9) and decreased with increasing age (HR=2.43; 95%CI: 1.5; 3.9 for those aged 70 to 79 years and HR=7.20; 95%CI: 4.5;11.5 for those aged 80 years and over). Final considerations: The present study advanced in describing the indicators of incidence, mortality and survival of prostate cancer in the municipalities of Cuiabá and Várzea Grande. A reduction in the incidence rate and stability of mortality was observed, as well as a higher specific survival probability than in other Brazilian studies, although lower than that observed in developed countries. From the analyzes carried out, it is possible to conclude that, despite advances in diagnosis and treatment, prostate cancer requires confrontation.